Thomas Weisel Partners : an IPO breathed new life into a West Coast investment bank, but where should the firm go from there? - Mitkowski, Allison; Manson, Mark; Elias, Jaan ([London] : SAGE, 2016)
The West Coast investment bank Thomas Weisel Partners (TWP), founded by the legendary Silicon Valley entrepreneur Thomas Weisel, enjoyed one of the most successful start-ups of a financial services firm in history. Valued at $500 million when it opened for business in January 1999, TWP-which focused its efforts primarily on the technology industry-raked in $662 million in net revenues during its first two years and executed deals for high-profile clients like Yahoo! and MapQuest.com. But in 2001, the private boutique firm was hit hard by the implosion of the dot-com, telecom and technology industries, which comprised the bulk of the TWP's investment banking business. The downturn in the economy led Weisel to restructure his business. This case study examines this topic.
Originally Published in: Mitkowski, A., Manson, M., & Elias, J. (2007). Thomas Weisel Partners: An IPO Breathed New Life Into A West Coast Investment Bank, But Where Should The Firm Go From There? 07-034. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Thomas Weisel Partners; Business enterprises -- Finance -- Case studies; Corporations -- Finance -- Case studies; Investment banking -- United States -- Case studies; Strategic planning -- Case studies